SOSIALISASI PEDULI PENYANDANG DISABILITAS: KESETARAAN HAK DALAM SISTEM PENDIDIKAN DI SMA NAMIRA MEDAN - Pardede, Lukman; Pardede, Dewi Lestari; Sinurat, Hersakso; Laia, Didi Yusuf Friend (Lembaga Penelitian dan Pengabdian Pada Masyarakat (LPPM) Universitas Darma Agung (UDA) Medan, 2023)
The rising number of disabilities in Indonesia, currently at 22.97 million, equivalent to 8.5% of the population, highlights the urgent need for inclusive education. Despite constitutional and international commitments to non-discrimination, people with disabilities face challenges in accessing higher education due to exclusionary admission practices. This paper reveals discriminatory criteria in brochures, limiting the choice of majors for disabled students.The research exposes the pervasive stigma against disabilities, resulting in social marginalization and denial of equal educational opportunities. These discriminatory practices extend to public facilities, legal standing, and violate basic human rights. Despite constitutional guarantees and global commitments, challenges persist in providing effective educational programs and services for all individuals with disabilities. This study explores the educational disparities faced by people with disabilities, assessing student awareness at Namira Private High School and examining the role of formal education in promoting inclusivity. The conclusion emphasizes the need for collective efforts to eliminate internal and external barriers hindering the full realization of educational rights for people with disabilities. The findings underscore the existing gaps and encourage actions to ensure equal opportunities for people with disabilities in education.